Сравнительный анализ накопителей энергии для транспортных средств - Любарский, Борис Григорьевич; Шайда, Виктор Петрович; Буряковский, Сергей Геннадиевич (Державне підприємство "Державний науково-дослідний центр залізничного транспорту України", 2015)
В статье рассмотрены наиболее распространение типы накопителей энергии, используемые для транспортных средств. Показано, что существующие критерии не могут дать полную оценку накопителей энергии для автономных транспортных средств, т.к. не учитывают транспортную составляющую. Предложено дополнить существующие критерии тремя новыми (доработанными) показателями, которые учитывают затраты на транспортировку накопителей энергии. Выполнен анализ накопителей энергии, которые используются на конкретных транспортных средствах, с учетом предложенной системы критериев.

At present, in the majority of autonomous vehicles, the energy source is power units based on internal combustion engines. As known, such power units provide optimum economical operation in only one power, speed and temperature operating mode, and in other modes, their energy effi ciency (fuel consumption) is much, sometimes several times, lower than in the optimal mode. Therefore, the greatest prospectives in the fi eld of energy savings lie in the research that will allow the internal combustion engine work in the optimal mode under all motion modes of a vehicle. The coeffi cient of effi ciency of the transport system with non-autonomous vehicles that draw power from a contact network are largely dependent on the relative position of vehicles and traction substation. Being near substations or working in stopping mode and not regenerative braking, traction network losses are low, still in the other modes they can reduce the overall effi ciency of the system by tens of percent’s. One of the solutions to these problems is the use of energy storage devices that ensure economical operation of autonomous power plants, improve the dynamic performance of vehicles, and improve the effi ciency of their support systems. The paper presents the most common types of energy storage devices for vehicles: electrochemical, condensing, mechanical and pneumatic. The substantiation of criteria for evaluating the effectiveness of energy storage for vehicles, taking into account the cost of transporting them. The criteria suggested for assessing the energy storage of vehicles allow conducting comparative analysis of different, at nominal parameters and principles of action, devices, according to their use on vehicles where transport costs can be signifi cant. The conducted analysis of specifi c examples of energy storage devices and vehicles has led to the following conclusions: for the most of considered vehicles, the best performance based on the criterion of specifi c energy costs are gel batteries AGM, and in terms of specifi c power ratings cost - the mechanical energy storage.
Comparative analysis of the energy storage devices for vehicles
Keywords: автономные транспортные средства; накопитель энергии; критерии оценки эффективности; аккумулятор; ионистор; механический накопитель энергии; удельная мощность; удельные энергетические затраты; удельные мощностные затраты; autonomous vehicles; energy storage; performance benchmarks; battery; ionistor mechanical energy storage; power density; specific energy consumption; specific cardinality costs